Role of L-Carnitine and Herbal Methionine in Improving Meat Quality Traits and Economic Efficiency of Broiler Chicken Production - Mohamed, Mohammed Hasib; Mohammed, Diyar Jaafar (American Journal of Botany and Bioengineering, 2026)
The current study was carried out to determine the impact of dietary supplementation using L -carnitine and herbal prepared methionine, either as a single dietary supplement or in combination with each other, on the quality of meat characteristics and the financial stability of the broiler chicken production. The experiment involved Ross308 broiler chicks of randomly selected eight dietary treatments whose arrangement was completely randomized. Each of the experimental diets was created to meet the nutrient requirements and used 5‛ percent sunflower oil as the source of fat. Meat samples at the end of the 42 days of the experimental period were to be harvested in order to determine chemical composition, water-holding capacity, and sensory evaluation and also an evaluation of economic efficiency in terms of feed cost per kilogram of live body weight. The results revealed that both L-carnitine and herbal produced methionine supplementation had a significant alteration on the chemical characteristics of the meat based on the higher level of crude protein and lower level of fat in the sample of both the breast and thighs of the meat compared to the control diet. There was also a significant improvement in the supplemented groups in terms of water-holding capacity and sensory properties, which are colour, texture, flavour, taste and overall acceptability. In addition, the combination treatment was the most efficient in terms of relative economic efficiency thus signaling an increase in profitability. Altogether, broiler diets supplemented with L-carnitine and herbally derived methionine, and especially when used simultaneously is an effective nutritional intervention to improve meat quality traits and increase the economic gain of broiler production.